Malaysia and the cold war era - Ooi, Keat Gin 1959- (Routledge studies in the modern history of Asia, 2020)
From the end of the Second World War in 1945 to the collapse of the Soviet Union in 1991, there was a great deal of turmoil, tension, and violence in what became Malaysia as a result of the 1963 Federation, upheavals included the Malayan Emergency of 1948-60, the independence of Malaya in 1957, Konfrontasi with Indonesia of 1963-66, the Philippines claim to Sabah, the Sarawak Communist Insurgency (1962-90) and the Second Malayan Emergency of 1968-89. This book breaks new ground in arguing for a longer trajectory of the Cold War tracing this phenomenon back to 1920s colonial Malaya and Sarawak. Many new research findings showing how Malaysia coped with and overcame the many trials, challenges, and difficulties are presented hence further enriching the historiography.